COLLABORATION AND LONG-TERM RELATIONSHIPS IN CONSTRUCTION - Calistus AYEGBA; Xebiso B KAMUDYARIWA; David ROOT (Journal of Construction Project Management and Innovation)
There is increasingly a shift away from traditional contracting practices to collaboration and long-term relationships (CLR) contracts in the construction industry. The purpose of this article is to examine dimensions of CLR practices from a construction perspective. The research methodology employed is based on desk research. This involves the collection of secondary data on CLR practices. NVivo Pro 2011 software was used to aid analysis of the multiple articles. The findings indicate that top management commitment, a willingness to learn from and to support the parties, mutual trust, complete integration of project team members, and efficient and open communication are some of the requirements for CLR. The procurement strategies that internalise CLR practices in construction are reported to be framework contracts, partnership, and alliance contracting. However, these approaches are shown to be appropriate for specific kinds of clients, suppliers and projects. Consequently, the selection of parties to go into these procurement strategies for CLR becomes critical to achieve the benefits that CLR has been shown to deliver. This will ensure that scarce resources are only dedicated to relationships and processes that will genuinely benefit and support CLR. The knowledge and understanding generated by the study will be useful in encouraging construction stakeholders to appreciate the need for CLR practices and to embrace CLR approaches.